Analysis of the Difficulty in Performing the Volleyball Bottom Passing Technique at the Sahabat Muda Club - Amelia Afriyanti; Helvi Darsi; Ever Sovensi (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the difficulty of the underhand passing technique of the Sahabat Muda club in Lubuklinggau City and to determine the factors causing the difficulty of athletes doing the underpassing of the Sahabat Muda club in Lubuklinggau City. This research is a qualitative descriptive research that explains the situation or ongoing activities by conducting interviews. In this study, the population was 15 people and the sample consisted of 10 people who took part in volleyball training activities at the Young Friends Club. Data collection techniques using observation and interviews to determine the difficulties and factors of difficulty of each individual. The results of this study indicate that the description 1) The error that usually occurs when doing a downward pass is that the position of both arms is too high. When receiving the ball, both knees are not bent. The arms are not tight, the ball hits the upper arm. 2) The cause is due to an error in positioning the batting arm bent at the elbow so that the bat is narrow, as a result the ball rotates or turns its direction. Improper impact of the ball on the palm of the hand. At the time of contact with the ball the arms are not parallel. There is no harmonious or simultaneous movement of the arm and leg movements. Too explosive movement of the swing as a whole, so the ball is far off the mark. Knees are less bent in the preparation step of implementation. Hit or contact the ball with the forearm too late so that the direction of the ball is up and back. The high ball that should have been in the top pass, but was taken with the bottom pass, so it is not accurate at the intended target. Less able to regulate contact with the ball quickly, according to the arrival of the ball...